Soil properties and nutrient uptake of maize (Zea mays) as influenced by mixed manure and blended inorganic fertilizer in Haramaya district, eastern Ethiopia - Dejene Teressa; Kibebew Kibret; Nigussie Dechasa; Lemma Wogi (Heliyon, 2024)
The deteriorating state of soil fertility and low agricultural productivity in Ethiopia can be traced to the lack of equivalent consideration given to the soil's biological, chemical, and physical properties. A pot experiment was conducted to investigate the effect of mixed manure and blended nitrogen, phosphorus, sulfur and boron (NPSB) fertilizer on phosphorus adsorption, and other properties of Vertisols, nutrient uptake, and growth performance of maize. The study findings indicate that the combined application of mixed manure and blended NPSB significantly reduced soil pH from 7.87 to 7.68, phosphorus adsorption efficiency from 93 to 88.5 %, and Freundlich adsorption capacity from 194 to 100.75 mg kg−1 , intensity from 1.96 to 1.27 compared to control. However, combined application of these two treatments significantly increased the organic carbon from 0.81 to 1.64 %, total nitrogen from 0.04 to 0.13 %, and available phosphorus from 6.96 to 73.82 g kg−1. The study further revealed that mixed manure and blended NPSB resulted in significantly (p ≤ 0.05) higher contents of nitrogen and phosphorus in the maize leaves as well as their uptake compared to their sole application and control. The highest values of these parameters were observed in plots treated with a combined application of 15 t ha−1 mixed manure with each rate of 100 and 150 kg ha−1 blended NPSB. Additionally, the maize plant height (p ≤ 0.05) and above-ground biomass (p ≤ 0.01) also exhibited significant increase. Compared to the control and full dose of NPSB, all the treatments that received a combined application of 15 t ha−1 mixed manure with blended NPSB ranging from 50 to 150 kg ha−1 resulted in significantly higher above-ground biomass of maize. The results suggest that the combined use of mixed manure and blended NPSB could be a practical and effective approach to improve soil properties and maize above-ground biomass yield.